Perdeuteration of cholesterol for neutron scattering applications using recombinant Pichia pastoris. (May 2018) - Moulin, Martine; Strohmeier, Gernot A.; Hirz, Melanie; Thompson, Katherine C.; Rennie, Adrian R.; Campbell, Richard A.; Pichler, Harald; Maric, Selma; Forsyth, V. Trevor; Haertlein, Michael
Highlights: In vivo production of perdeuterated cholesterol using a lipo-engineered yeast strain. Perdeuterated cholesterol has been purified and characterised. Application of perdeuterated cholesterol for neutron scattering studies has been demonstyrated. Abstract: Deuteration of biomolecules has a major impact on both quality and scope of neutron scattering experiments. Cholesterol is a major component of mammalian cells, where it plays a critical role in membrane permeability, rigidity and dynamics, and contributes to specific membrane structures such as lipid rafts. Cholesterol is the main cargo in low and high-density lipoprotein complexes (i.e. LDL, HDL) and is directly implicated in several pathogenic conditions such as coronary artery disease which leads to 17 million deaths annually. Neutron scattering studies on membranes or lipid-protein complexes exploiting contrast variation have been limited by the lack of availability of fully deuterated biomolecules and especially perdeuterated cholesterol. The availability of perdeuterated cholesterol provides a unique way of probing the structural and dynamical properties of the lipoprotein complexes that underly many of these disease conditions. Here we describe a procedure for in vivo production of perdeuterated recombinant cholesterol in lipid-engineered Pichia pastoris using flask and fed-batch fermenter cultures in deuterated minimal medium. Perdeuteration of the purified cholesterol was verified by mass spectrometry and its use in a neutron scattering study was demonstrated by neutron reflectometry measurements using the FIGARO instrument at the ILL.